Scaling and balancing carbon fluxes in a heterogeneous tundra ecosystem of the Lena River Delta - Rößger, Norman (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2018)
The Arctic tundra has been a carbon sink through the comprehensive accumulation of carbon in permafrost-affected soils over thousands of years. This carbon may be remobilised in the course of climate change, which occurs more pronounced in the Arctic region than on the global average. With growing concern about rising emissions of the greenhouse gases methane and carbon dioxide, the current and prospective carbon turnover of the terrestrial Arctic is regularly assessed. However, these assessments are associated with large uncertainties, which can (inter alia) be ascribed to both the general shortage of flux data from the vast and sparsely inhabited Arctic region, and the typically high spatiotemporal variability of carbon fluxes in tundra ecosystems. Thus, this study aims at providing robust carbon budgets from a Siberian tundra landscape that has not yet been investigated: an active flood plain situated in the Lena River Delta. Applying the eddy covariance methodology, methane and carbon dioxide fluxes were determined during the growing seasons 2014 and 2015. These fluxes exhibited a great deal of temporal variability, which was, besides seasonal variation, largely the result of the pronounced spatial variability of soil and vegetation characteristics within the footprint. In order to explain this flux variability, the vegetation of the entire flood plain was classified utilising a high-resolution orthomosaic. In this process, three vegetation classes were designated accounting for shrubs (large Salix spp.), sedges (Carex spp., Eriophorum sp., Equisetum sp.) and intermediate (low Salix spp., Carex spp.) vegetation. These classes were well coupled with environmental variables such as soil moisture, moss properties and active layer depth. Hence, the vegetation served as an integrated proxy for potential soil-related flux drivers, whose contribution to the flux signal permanently varied according to the shifting source area. Applying footprint information in the form of relative contributions of vegetation classes ...